High rate of hypoglycemia in 6770 type 2 diabetes patients with comorbid dementia: A multicenter cohort study on 215, 932 patients from the German/Austrian diabetes registry. (February 2016) - Prinz, Nicole; Stingl, Julia; Dapp, Albrecht; Denkinger, Michael D.; Fasching, Peter; Jehle, Peter M.; Merger, Sigrun; Mühldorfer, Steffen; Pieper, Urte; Schuler, Andreas; Zeyfang, Andrej; Holl, Reinhard W.; et al.
Highlights: Real-life data analysis of a large number of German/Austrian elderly T2D patients. Demented T2D patients had a higher rate of hypoglycemia and used insulin more often. Metabolic control was comparable between patients with or without dementia. Hypoglycemia risk due to tight glycemic control exceeds benefits in T2D with dementia. Abstract: Aims: Dementia and type 2 diabetes (T2D) are two major phenomena in older people. To compare anti-hyperglycemic therapy and diabetes-related comorbidities between elderly T2D patients with or without comorbid dementia. Methods: 215, 932 type 2 diabetes patients aged ≥40 years (median [Q1 ;Q3 ]: 70.4 [61.2;77.7] years) from the standardized, multicenter German/Austrian diabetes patient registry, DPV, were studied. To identify patients with comorbid dementia, the registry was searched by ICD-10 codes, DSM-IV/-5 codes, respective search terms and/or disease-specific medication. For group comparisons, multiple hierarchic regression modeling with adjustments for age, sex, and duration of diabetes was applied. Results: 3.1% ( n  = 6770; 57% females) of the eligible T2D patients had clinically recognized comorbid dementia. After adjustment for demographics, severe hypoglycemia (insulin group: 14.8 ± 0.6 vs. 10.4 ± 0.2 events per 100 patient-years, p  < 0.001), hypoglycemia with coma (insulin group: 7.6 ± 0.4 vs. 3.9 ± 0.1 events per 100 patient-years, p  < 0.001), depression (9.9 vs. 4.7%, p  < 0.001), hypertension (74.7 vs. 72.2%, p  < 0.001), stroke (25.3 vs. 6.5%, p  < 0.001), diabetic foot syndrome (6.0 vs. 5.2%, p  = 0.004), and microalbuminuria (34.7 vs. 32.2%, p  < 0.001) were more common in dementia patients compared to T2D without dementia. Moreover, patients with dementia received insulin therapy more frequently (59.3 vs. 54.7%, p  < 0.001), but metabolic control (7.7 ± 0.1 vs. 7.7 ± 0.1%) was comparable to T2D without dementia. Conclusions: In T2D with dementia, higher rates of hypoglycemia and other diabetes-related comorbidities were observed. Hence, the risks of a glucocentric and intense diabetes management with insulin and a focus on tight glycemic control without considering other factors may outweigh the benefits in elderly T2D patients with comorbid dementia.